Implementasi online peer asisted learning dalam pembelajaran keterampilan klinik pada mahasiswa keperawatan - Aris Setyawan (Health Sciences and Pharmacy Journal, 2019)
Peer-assisted learning (PAL) has been shown to help improve clinical skills. Nevertheless, the PAL method has not been able to provide sufficient training opportunities for participant students due to space and time constraints. The existence of technological developments in the field of education, a new opportunity for lecturers to answer the needs and create innovation using online Peer-assisted learning in supporting the learning process. The purpose of this research was to know difference of clinical skill value of student and learning motivation of student before and after the application of Online peer assisted learning method. The type of this research was quantitative with quasy experimental pre-test and post-test with control group design. The study was conducted in Nursing Study Department of STIKes Surya Global Yogyakarta with a 70 sample from second year students which randomly is devided into control and intervention group. The intervention group was given a peer-assisted learning (PAL) model with the help of video call technology in WhatsApp application. Control group with peer-assisted learning face to face model has ben done usualy. A checklist of clinical skills of thoracic examination and questioner of learning motivation was used as instrument. The result of this research was the mean value of the intervention group learning motivation was 100,6 while the mean value of the learning motivation of the control group was 95,02. The mean value of clinical skills in the pre-test control group of 82,45 and the mean post-test increased to of 87,41. The clinical skill delta value of the intervention group was 5,04 while the control group's delta value was 4,76. The conclusion was the OPAL method has been shown to increase learning motivation and the value of clinical skills of thoracic physical examination in nursing students